2013
DOI: 10.1136/jclinpath-2012-201425
|View full text |Cite
|
Sign up to set email alerts
|

Frequent expression of follicular dendritic cell markers in Hodgkin lymphoma and anaplastic large cell lymphoma

Abstract: This study confirmed the frequent expression of FDC markers in HL and ALCL. Especially, GLI3, fascin and TUBB3 are the most sensitive markers. Further studies are required to evaluate the association between FDCs, HRSs and ALCL cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Previously, to conduct studies related to biomarker positivity, researchers would first establish a hypothesis and verify it through clinical experiments, or conduct a long process of directly searching for, extracting, and collecting data through the hospital EMR and parsing the data before analysis [22][23][24][25]. Researchers often experience difficulties in securing such large volumes of data.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, to conduct studies related to biomarker positivity, researchers would first establish a hypothesis and verify it through clinical experiments, or conduct a long process of directly searching for, extracting, and collecting data through the hospital EMR and parsing the data before analysis [22][23][24][25]. Researchers often experience difficulties in securing such large volumes of data.…”
Section: Discussionmentioning
confidence: 99%
“…The lineage infidelity of Hodgkin/Reed-Sternberg cells (HRSs) often causes diagnostic problems as HRS markers are also favorable for follicular dendritic cells (FDCs). Investigation of the expression of FDC markers in HL and anaplastic large cell lymphoma (ALCL) revealed GLI3, fascin (actin-bundling protein found in membrane ruffles), and TUBB3 (a member of the beta-tubulin protein family) as the most sensitive markers, which were diffusely positive in HL [238]. A recent study from our lab reported the increased expression of GLI1 in KSHV infected primary effusion lymphoma (PEL) cells [239].…”
Section: Hh Signaling Pathways During Infections and Viral Malignanciesmentioning
confidence: 98%
“…A typical example is CHL, wherein tumour cells show unique immunophenotypic features, whose mechanisms have been explained by complex genetic alterations and activations of various signal pathways through interaction with microenvironmental cells 8 . The rare type of CHL may be positive for CD21, S100, and/or fascin, all of which are normally expressed by dendritic cells and/or macrophages, whereas representative markers for CHL, such as CD30 or PAX5, may be lost or expressed in a weaker and scattered manner 8–11 . These atypical CHL cases could be challenging and require more definitive findings to verify the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…8 The rare type of CHL may be positive for CD21, S100, and/or fascin, all of which are normally expressed by dendritic cells and/or macrophages, whereas representative markers for CHL, such as CD30 or PAX5, may be lost or expressed in a weaker and scattered manner. [8][9][10][11] These atypical CHL cases could be challenging and require more definitive findings to verify the diagnosis. Among the non-neoplastic cells, activated T and B lymphocytes as well as endothelial cells and macrophages may be positive for CD30.…”
Section: Discussionmentioning
confidence: 99%